Implementation of Virtual Practicum in the learning process of MIPA (Mathematics and Natural Sciences) in the Pandemic Period, Case Study on Junior High School in Lhokseumawe City - Muhammad, Iryana; Fatmi, Nuraini (International Conference on Sciences Development and Technology, 2021)
This research was conducted in a junior high school in Lhokseumawe City. Based on the results of early observations of the study, virtual practicum activities are still rarely conducted in a number of schools in Lhokseumawe City. To pursue the government programs, learning has been shifted to online classes, so that the students can still get their right to acquire knowledge but stay safe at home during pandemics. The condition of online learning during pandemic providing efficiency of time and carrying out health protocols habit, but basically emerge several urgent problems among teachers, students and parents. This research type is descriptive in the form of case studies. This research is conducted deeply on a situation or condition in a systematic way starting from making observations, collecting data, analyzing information, and reporting results. Based on the results of interviews, it can be concluded that schools in Lhokseumawe have implemented online learning, planning online learning by preparing syllabus, lesson plans, and teaching materials. The results of this closed questionnaire research are used to find out things that support the implementation of virtual practicum. From the results of the questionnaire, it is known that the implementation of learning through the virtual practicum module is very effective, this can be seen from the final report of the students' practicum score are 100%, which means students understand the use of virtual modules. and able to make a final practicum report perfectly